"The world will be made whole": Love, Loss, and the Sacramental Imagination in Marilynne Robinson's Housekeeping. (June 2017) - Potts, Matthew
In this article I suggest that attending to the water imagery in Marilynne Robinson's novel Housekeeping can reveal a sophisticated account of the sacraments, one that anticipates by several years important developments in recent Christian theology. I also argue that the novel seems thus to suggest something crucial about the nature of literary representation itself, about writing's relationship to the reality of love. Briefly put, in Housekeeping Marilynne Robinson not only proposes a novel sacramental theology and anticipates its development in other thinkers, she also suggests a sort of sacramentality inherent to the very act of literary writing.